Pemodelan Matematika Opsi Saham Karyawan Menggunakan Metode Trinomial yang Memperhitungkan Efek Dilusi - Vina Rosalina; Rudianto Artiono (MATHunesa: Jurnal Ilmiah Matematika, 2023)
Stock options are contracts involving two parties, namely the option seller (writer) and option buyer (holder), where the rights of the option buyer (holder) will be guaranteed by the option seller (writer) in selling or buying shares at an agreed price. (strike price) before or at maturity time. One type of development of stock options, namely Employee Stock Options (OSK) or commonly called Employee Stock Options, is an option where the beneficiary cannot sell or transfer the options given by the company because these options function as rewards and incentives for their employees so that in this case, employees has the right to stock options but has no obligation to buy them. This study aims to model employee stock options that take into account the dilution effect. The dilution effect is a decrease in the percentage of share ownership due to an increase in the total number of shares, but the investor does not participate in the issuance of new shares. This study uses the trinomial method where stock price movements will be seen by calculating forward and determining the option value backwards. For this method, the stock price movement model has three possible events, namely the stock price moves up, stays, or falls. This research produces a mathematical model that is used in determining the price of employee stock options by taking into account the dilution effect. Keywords: Employee Stock Options, Trinomial Method, Dilution Effects